2020
DOI: 10.2147/ott.s244351
|View full text |Cite
|
Sign up to set email alerts
|

<p>Comprehensive Analysis of <em>CDC27</em> Related to Peritoneal Metastasis by Whole Exome Sequencing in Gastric Cancer</p>

Abstract: The peritoneum is the most common metastatic site of gastric cancer and is associated with a dismal prognosis. However, there is no reliable biomarker for predicting peritoneal metastasis (PM). Materials and Methods: Whole-exome sequencing (WES) was performed on formalinfixed, paraffin-embedded (FFPE) samples from 63 patients with stage I-III gastric cancer and circulating tumor DNA (ctDNA) samples from 10 patients with stage IV gastric cancer. Differentially expressed genes (DEGs) were identified between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The COSMIC database includes several deregulations and mutations of this gene that are associated with embryonal tumours, suggesting a critical and primal role of this gene in driving paediatric tumorigenesis (7,25,26). Furthermore, previously identified mutations in CDC27 were shown to significantly correlate with progressive disease, low overall survival and diseasefree survival (23,27). The second gene with the most frequent TCB variants was the CTBP2 gene.…”
Section: Discussionmentioning
confidence: 99%
“…The COSMIC database includes several deregulations and mutations of this gene that are associated with embryonal tumours, suggesting a critical and primal role of this gene in driving paediatric tumorigenesis (7,25,26). Furthermore, previously identified mutations in CDC27 were shown to significantly correlate with progressive disease, low overall survival and diseasefree survival (23,27). The second gene with the most frequent TCB variants was the CTBP2 gene.…”
Section: Discussionmentioning
confidence: 99%
“…AHNAK2 and CDC27 mutations have been reported to be closely linked to progression of patients with unresectable metastatic GC, and to tumorigenesis and progression by supporting epithelial-mesenchymal transition (EMT) and gaining tumor cell-like properties (17,18). CDC27 was reported to be associated with a higher risk of peritoneal metastasis and poor survival in GC (19), suggesting that patients with this mutation may benefit from immunotherapy. We found that somatic mutation of ATAD3B was related to tumor metastasis, which may provide opportunities for future study.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advancements in NGS techniques have identified various nucleotide mutations associated with GC (Table II). The top mutated genes showing higher mutation frequency were TP53, TTN, MUC16, CDH1, KMT2C and MLH1 (31)(32)(33). In 1977, Leon et al (34) reported that numerous patients with cancer had elevated circulating cfDNA, and found that this DNA was tumor derived.…”
Section: Detection Of Genetic Alteration Of Circulating Tumor Dna (Ctmentioning
confidence: 99%